Pengaruh Gaya Mengajar Self-Check dengan Pendekatan Deep Learning Terhadap Kejujuran dan Health-Related Fitness Peserta Didik MAN 2 Kota Banjarmasin - Ayu Oktolita Pertiwi; Syamsul Arifin; Mashud Mashud (Jurnal Porkes, 2026)
This study aims to determine the effect of the Self-Check teaching style with a Deep Learning approach on students’ honesty and Health-Related Fitness at MAN 2 Kota Banjarmasin. This research with a quasi-experimental method using a pretest-posttest control group design. The population consisted of tenth-grade students of MAN 2 Kota Banjarmasin, with a sample of 60 students divided into an experimental group and a control group, each consisting of 30 students. The instruments used were a validated honesty questionnaire and Health-Related Fitness tests, including body mass index, sit-up, push-up, sit and reach, and bleep test. Data were analyzed using descriptive analysis and paired sample t-test. The results showed that the experimental group experienced an increase in Health-Related Fitness from 14.70 to 17.40, while the control group increased from 14.67 to 15.30. In terms of honesty, the experimental group increased from 62.07 to 64.47 with a significance value of 0.001, while the control group increased from 61.73 to 61.97 with a significance value of 0.006. These findings indicate that the Self-Check teaching style with a Deep Learning approach has a positive effect on improving students’ honesty and Health-Related Fitness.